Hedgeing and the use of derivatives: A study of US NOn-financial Companies - Zhong, Yina (2006)
This paper provides empirical evidence on determinants of corporate derivatives usage for hedging purpose by US Fortune 100 Companies. Logit regression model is used to test whether the relationships between financial characteristics and the likelihood of using derivatives are consistent with the hedging hypotheses. Data about corporate derivative activities are obtained from companies 2005 annual reports. Based on the statistical results, there is no significant difference on the financial characteristics between those use derivatives for hedging and those do not. Also, the evidence is consistent with respect to the substitutes for hedging with derivatives. Finally, other evidence suggests that the expected cost of financial distress is one of the main reasons on firm's decision to use derivatives.